Risk Behaviour in Adolescence Patterns, Determinants and Consequences - Richter, Matthias; SpringerLink (Online service) (Wiesbaden : VS Verlag für Sozialwissenschaften, 2010)
Adolescents are generally thought to be healthy. However, adolescent risk behaviours, such as substance use, a poor diet or early sexual activity, are topics that keep generating high academic and media interest. Despite considerable explanatory efforts, not much is known yet about the proximate and distal determinants as well as the psychosocial and health-related consequences of risk behaviour in adolescence. The study is among the first to systematically examine the antecedents and consequences of risk behaviour from a comparative perspective over time and across countries. Matthias Richter presents findings from several empirical studies and extends current theoretical and empirical knowledge on adolescent risk behaviour. This book is valuable reading for academics, practitioners and policy makers in a range of disciplines: sociology, psychology, educational sciences, public health and nursing sciences, with a special focus on adolescent risk behaviour.
Conceptual framework -- Material and methods -- Results of the empirical studies -- Discussion and perspectives.
Keywords: Social sciences; Sociology; Social Sciences; Sociology; Education (general).; Sociology